Citizen science on a smartphone: Participants' motivations and learning. (January 2016) - Land-Zandstra, Anne M.; Devilee, Jeroen L. A.; Snik, Frans; Buurmeijer, Franka; van den Broek, Jos M.
Citizen science provides researchers means to gather or analyse large datasets. At the same time, citizen science projects offer an opportunity for non-scientists to be part of and learn from the scientific process. In the Dutch iSPEX project, a large number of citizens turned their smartphones into actual measurement devices to measure aerosols. This study examined participants' motivation and perceived learning impacts of this unique project. Most respondents joined iSPEX because they wanted to contribute to the scientific goals of the project or because they were interested in the project topics (health and environmental impact of aerosols). In terms of learning impact, respondents reported a gain in knowledge about citizen science and the topics of the project. However, many respondents had an incomplete understanding of the science behind the project, possibly caused by the complexity of the measurements.